PERUBAHAN KUHP (CRIMINAL CODE) FEDERASI RUSIA DAN KEBIJAKAN MOBILISASI TERBATAS DALAM OPERASI MILITER KHUSUS RUSIA DI UKRAINA - Fitjriyah, Khalishah; fahrurodji, ahmad (Multikultura, 2025)
This study discusses the amendments to the Criminal Code of the Russian Federation in the context of Russia's limited mobilization during the implementation of its special military operation in Ukraine. It is a multidisciplinary study that combines legal and cultural perspectives, using a qualitative literature review method with a normative legal approach. The objective of this research is to analyze the changes in Russia's criminal code aimed at anticipating the impacts of limited mobilization. By applying the theory of criminalization, the study finds that the amendments and additions to existing legal norms are part of the state's efforts to protect its citizens from the direct and indirect consequences of a military emergency. The criminalization policy is closely related to Russia’s political tradition and President Putin’s policy strategy, which is reflected in the concept of the “dictatorship of law.”